The Value of Serial Measurement of Arterial Stiffness in Cardiovascular Disease - Hack-Lyoung Kim (Reviews in Cardiovascular Medicine, 2024)
Clinically assessing arterial stiffness is valuable because it aids in predicting future cardiovascular events. There are several methods for measuring arterial stiffness, including pulse wave velocity (PWV), augmentation index, and pulse pressure. Numerous studies have shown that these indicators of arterial stiffness possess prognostic value for various patient groups as well as the general population. In cross-sectional studies, arterial stiffness was also linked to organ damage indices. However, most studies related to arterial stiffness have relied on a single measurement. Taking multiple serial measurements of arterial stiffness offers several advantages. Through repeated assessments, one can confirm the variability of arterial stiffness and observe changes over time, which is beneficial for understanding its pathophysiology. Such repeated measurements are also invaluable in evaluating the efficacy of interventions aimed at improving arterial stiffness. However, caution is needed, as there is no standardized method for measuring arterial stiffness. For instance, with PWV, the values can be influenced by numerous external factors. Therefore, the external conditions during the measurement must be noted. It’s essential to recognize the pros and cons of repeated arterial stiffness measurements and integrate them effectively into clinical practice.